MENINGKATKAN KUALITAS TIDUR IBU HAMIL TRIMESTER 3 DENGAN SLEEP ON SIDE MENGGUNAKAN BUKLET - Andriani, Dewi; Sholihah, Wardatus; Mahundingan, Rosari Oktaviana (PPM STIKES Adi Husada, 2024)
Introduction & Aim: Pregnant women in the third trimester will experience physiological changes in the reproductive system as the gestational age increase, and are followed by psychological changes that each person feels differently. The increase in abdominal volume as pregnancy progresses causes discomfort until delivery approaches and can disrupt the quality of sleep. Sleep quality disorders experienced by pregnant women in the third trimester will cause a decrease in body resistance, thus risking the labor process and fetal health. Non-pharmacological treatment is the right choice to prevent side effects for the fetus. Sleep on side for pregnant women in the third trimester can reduce pressure on the inferior vena cava so that the fetus gets an optimal healthy blood supply. Education with booklet can help more easily understande and practice sleeping position on side. The aim of this activity is to help pregnant women in the third trimester to fulfill their sleep needs independently. Method of Activity: This activity is carried out on pregnant women in the 3rd trimester and assisted by community health workers in the RW 08 Sawahpulo, Ujung Village, Semampir District, Surabaya. Results: Showed an increase in the level of knowledge of pregnant women in trimesters 3rd with sleeping on side with good category of 100% (19 respondents). Discussion: Education sleep on side improving sleep quality in pregnant women in trimester 3rd using booklet received positive response from respondents, so that the knowledge and behavior of pregnant women increased in meeting sleep needs